Comparative Study for the Levels of Trace Elements in Water from Southern Part of Iraq during 1996 – 2010 - H.Mohammed, Muayad (University of Thi-Qar Journal of Science, 2012)
A comparative study for the levels of trace elements in water from southern part of IRAQ for the period of time 1996 to 2010 was carried out to investigate the quality of waters. The study is based on the chemical analysis of trace elements: Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb and Zn. For subsurface water samples covered 12 stations along Al-Izz , Tigress, Euphrates, Shatt Al-Arab, Khor Al-Zubair, Shatt Al-Basrah and Main Outlet Drainage (MOD) rivers. Spectrophotometry was adopted for this analysis. The results showed that levels of trace elements were between those for dissolved phase and particular matter of water in region which normally analyzed by atomic spectrometer. Trace elements concentrations reported by this study were higher than allowed levels by WHO and IRPR without any classification of the phase studied. Fluctuation of elements concentrations in the area attributed to metal input as well as geochemical and hydrologicalcharacteristics of the water.